2018
DOI: 10.1155/2018/1732906
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study: Environmental Assessment of Perchloroethylene in Dry-Cleaning Facilities in the UAE

Abstract: Background Perchloroethylene (PERC) is a widely spread cleaning solvent, used in nearly all dry-cleaning facilities. It has been declared as “probable human carcinogen” by the International Agency for Research on Cancer (IARC) due to its hazardous and toxic effects on human health. The study aimed at assessing the exposure of PERC among dry-cleaning workers at four different dry-cleaning facilities in the UAE. Methods The four dry-cleaning facilities, using PERC in one of the cities of the UAE, were selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Direct skin contact with liquid PERC may lead to erythema, papules and burns (19) . Furthermore, the findings of other study also demonstrated that the dry-cleaning workers exposed to PERC are at risk of developing acute or chronic adverse health effects, depending on the concentrations of PERC (13) . Other principle finding of the present study was a non-significant alteration in the hematological parameters in PERC-exposed dry cleaning workers compare with the non-exposed group.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Direct skin contact with liquid PERC may lead to erythema, papules and burns (19) . Furthermore, the findings of other study also demonstrated that the dry-cleaning workers exposed to PERC are at risk of developing acute or chronic adverse health effects, depending on the concentrations of PERC (13) . Other principle finding of the present study was a non-significant alteration in the hematological parameters in PERC-exposed dry cleaning workers compare with the non-exposed group.…”
Section: Discussionmentioning
confidence: 77%
“…A preliminary study conducted by Habib et al (2018) has concluded that PERC is a widelyspread cleaning solvent, and the exposure of PERC among dry-cleaning workers is high. Therefore, installation of local exhaust ventilation systems and monitoring devices of PERC level is very important among dry-cleaning along with increase the awareness of workers about the harmful effects of PERC and the significance of using personal protective equipment (PPE) while performing their job such as wearing appropriate chemical resistant gloves and clothing, safety goggles with a face shield for eye protection and respirator for respiratory protection (13) . In some countries, manufacturers have begun using alternative cleaning methods that do not require the use of PERC (14) .…”
Section: Introductionmentioning
confidence: 99%
“…The development of a safety culture among dry cleaners focusing on proper solvent handling and workplace sanitation can also help to prevent potential toxic effects from tetrachloroethylene exposure. Fifth, the use of PPE like mask and hand gloves should be used correctly (Manuele, 2005;Lucas et al, 2015;Azimi et al, 2017;Habib et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This compound is a halogenated aliphatic hydrocarbon. [ 1–3 ] PEC is a solvent that is widely used in the dry cleaning industry. [ 4–6 ] Occupational exposure to it occurs via inhalation and skin contact in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that exposure to PEC in the workplace is associated with toxic effects on vital organs including the brain, lungs, liver, and kidneys. [3,10,11] According to The National Institute for Occupational Safety and Health (NIOSH), PEC is recognized as an occupational carcinogen and the International Agency for Research on Cancer (IARC) classifies it as a carcinogen in Group 2A. [7,12] Reports from the Occupational Safety and Health Administration (OSHA) show that exposure to levels above 100 ppm of PEC can be associated with damage to the brain system in humans.…”
mentioning
confidence: 99%